KOMITMEN ORGANISASI PENGURUS PONDOK PESANTREN DITINJAU DARI KARAKTERISTIK DEMOGRAFI - Muhammad Wardianto (Ilmu Psikologi Universitas Yudharta Pasuruan)
Islamic boarding school is one form of non-profit organization. In order to maintain it’s system, islamic boarding school purely supported by internal source. High organizational commitment become a variable which must be owned by every staf to increase productivity and suppress turnover in islamic boarding school’s stafs. The previous studies indicated an inconsistent result between the correlation of demographic variables and organizational commitment. In addition, research on organizational commitment in islamic boarding school’s stafs is still very rare, especially correlation with demographic variables. Population in this research is islamic boarding school’s stafs in Pasuruan Regency. The sample was taken proportionally and randomly from Ngalah Islamic Boarding School’s stafs, Pasuruan Regency. The data were collected with the Allen & Meyer's Organizational Commitment Scale that was modified and the scale at the same time contained a section to collect relevant demographic data of respondents. The results of this study indicate a significant correlation between gender and organizational commitment. It also found that age is positively correlated with organizational commitment. Meanwhile, the variable of education level and living years in islamic boarding school is not correlated with the organizational commitment of islamic boarding school’s stafs.